The Use of Bamboozle Website to Improve EYL Vocabulary Mastery - Amanah, Navisa Putri; Safitri, Cinta Amalia; Indriani, Lilia (Journal of English Language Teaching and Cultural Studies, 2025)
This study discusses using Bamboozle as a technology-based learning media to improve EYL vocabulary mastery. The Bamboozle website contains a variety of exciting games that can be utilized in learning. One of them is a quiz that displays images used by researchers in this study. This research uses quantitative methods with pre-experimental one-group pretest and posttest. The procedure of this design is giving a pretest, then giving treatment in the form of learning using Bamboozle, and then doing a posttest. This stage is used to see whether or not there is a change in the value that occurs before giving treatment (pretest) with the value after giving treatment (posttest). The research participants of this study were 5th-grade students consisting of 6 female students and six male students. The data processing results show a significant increase in pretest and posttest scores. The alternative hypothesis (Ha) is accepted because using the Bamboozle website can improve EYL vocabulary mastery.